Persepsi Stakeholders dalam Kesiapan dan Pelaksanaan Pelaporan Keuangan desa Berbasis Undang-Undang No.6 Tahun 2014 - Ravita Hanun, Nur (Akuntansi: Jurnal Akuntansi Integratif, 2020)
This research is to find out, describe and analyze stakeholder perceptions in the preparation and implementation of village financial reporting. This research is a qualitative research. The case study method approach was chosen to analyze social phenomena that exist in village financial reporting seen from stakeholder perceptions. Research informants consisted of key stakeholders, supporting stakeholders and key stakeholders. Data analysis uses triangulation techniques to reduce data, present data and draw conclusions. The results of this study indicate that the readiness and implementation in the preparation of village financial reporting affects the timing of the delivery of village financial statements. Stakeholders' perceptions state that village government is not ready to implement village financial reporting based on Law No. 6 of 2014 concerning Villages.